RONGGA MULUT SEBAGAI RESERVOIR POTENSIAL UNTUK INFEKSI Pseudomonas aeruginosa - Puspita Hajardhini; Heni Susilowati; Heribertus Dedy Kusuma Yulianto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Introduction : Pseudomonas aeruginosa (P. aeruginosa) is Gram-negative bacteria which is normally inhabiting in environment, however it tends to be an opportunistic pathogen within oral cavity. It utilizes the oral cavity as potential reservoir to infect either lungs or oral cavity itself. Both planktonic and biofilm forms can mediate its infection in oral cavity so that making its difficulties to eradicate since its broad resistance to antibiotics.Method : We review the pathogenesis of oral infection and host defense mechanism to P. aeruginosa as well.Discussion: Several prevention strategies, both chemical and nonchemical, are elaborated to avoid oral bacterial contamination.Conclusion : Prevention strategies in dental aspect to P. aeruginosa is highly needed as its occurrence are susceptible to cross-infection.